Dynamic stretching versus static stretching in gymnastic performance. A brief review - D'Anna, C.; Gómez Paloma, F. (Journal of Human Sport & Exercise, 2015)
Different types of stretching techniques are commonly performed in the gymnastic training sessions. Flexibility is one of the essential aspects of this sport like so the explosive strength but actually there is a limited literature assessing the effectiveness of the specific technique to increase the range of motion and, at the same time, to improve the explosive performance. The aim of this study was to conduct a brief analysis of the literature to understand how to plan the training programs finalized to improve the gymnastic performance (Gomez Paloma F., Rio L., D`Anna C. 2014). The MEDLINE and SportDiscus databases were searched for relevant literature using textwords for English-language articles related to stretching, flexibility, explosive strength, dynamic/static stretching and gymnastic. Additional references were reviewed from the bibliographies and from citation searches on key articles. Twenty-two articles were examined, of which two reviews, one roundtable discussion of flexibility training, two specific studies on gymnastics, two on basketball, one on baseball and the remaining articles focusing on the flexibility and the jumping performance in general. In accordance to several studies analyzed, the research carries out some reflections on different stretching techniques included in the training phases of gymnastics (warming-up, cooling down) useful in planning the training sessions finalized to the best performance. These are fundamental aspects to highlight and emphasize the consequences of the use of the different techniques especially regarding the duration and the intensity of the exercises choice.